OTIMIZAÇÃO DO MÉTODO DE EXTRAÇÃO DE CELULOSE NANOCRISTALINA PARA VALORIZAÇÃO DE RESÍDUOS LIGNOCELULÓSICOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Nanocrystalline cellulose is an aqueous suspension containing whiskers which have high crystallinity and high specific surface area. This material can be obtained from lignocellulosic fibers by means of an acid hydrolysis process. The characteristics of the nanocrystalline cellulose depends of the hydrolysis conditions, which may vary according to the following parameters: concentration of acid, fiber to acid ratio, temperature and reaction time. Therefore, the influence of these parameters was evaluated in a study conducted for the microcrystalline cellulose. From this, optimized conditions were determinated for obtaining nanocrystalline cellulose suspensions with maximum yield or high crystallinity index or high zeta potential. The nanocrystalline cellulose suspension which showed maximum yield was selected for the surface modification with a cationic surfactant and posteriorly submitted to the spray-drying process. The produced, microparticles are suitable for use in the composite processing by extrusion. Based on the optimized hydrolysis conditions, residues of pine wood and corncob were submitted to the process of nanocrystalline cellulose extraction. For this, it was necessary to carry out a procedure for the isolation of cellulose, which consisted of acetosolv pulping and bleaching. The results showed that was possible to extract nanocrystalline cellulose with suitable characteristics for use in industrial applications. Compared with the commercial microcrystalline cellulose, the residues provided a yield approximately 76.0% lower in the nanocellulose extraction. Therefore, further studies are necessary to improve this characteristic. Finally, the black liquor from acetosolv pulping was used for the lignin recovery. It is suggested that lignin can be used economically for the production of aromatic compounds.
Keywords: extração de celulose nanocristalina; resíduos lignocelulósicos; secagem por atomização; extraction of nanocrystalline cellulose; lignocellulosic residues; spray-drying; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA